Adaptive features of winter triticale accessions from the VIR collection - N. Sh. Garaeva; S. N. Ponomarev; M. L. Ponomareva (Труды по прикладной ботанике, генетике и селекции)
Background. In the context of global climate change, the study and development of genetic material with environmental plasticity and stability in the manifestation of its traits becomes relevant. The scientific and practical results achieved in triticale breeding place this crop among the most popular cereals in terms of economic importance. However, the main problem for the use of triticale in breeding practice is its limited genetic resources.Materials and methods. The research materials were 161 winter triticale (× Triticosecale Wittm. ex A. Camus) accessions from the global collection of VIR. The study and breeding-oriented assessment of the material were based on conventional breeding techniques and carried out according to the guidelines approved by VIR with minor amendments. The obtained research data underwent statistical analysis using the method by A. V. Kilchevsky and L. V. Khotyleva.Results. Environmental and genetic parameters were analyzed under the conditions of the Middle Volga Region of Russia. Genotypes were identified for their high general adaptability, i. e., securing the highest average yield in the entire set of environments. Cultivars were also selected for their least variable high yields under the impact of weather conditions. The analysis of the studied set of accessions showed that both high-yielding and low-yielding genotypes were stable. The character’s mean value and its environmental sensitivity were relatively independent and could be incorporated in one genotype in various combinations. This finding can be used in the process of triticale breeding.